Analisis Kebutuhan Media Ikonik Infografis dengan Bantuan Aplikasi Canva untuk Meningkatkan Kemampuan Berpikir Kronologis Siswa - Saputri, Saskia Eka; Yefterson, Ridho Bayu (Jurnal Kronologi, 2025)
This study aims to identify the need for developing iconic infographic media in history learning to support the enhancement of high school students' chronological thinking skills. Such skills are essential for understanding temporal sequences, causal relationships, and historical contexts coherently. The research employed a descriptive qualitative approach using observations, interviews, questionnaires, and pretests involving eleventh-grade students and a history teacher at SMAN 1 IV Koto. Findings show that learning activities remain dominated by text-based materials, while students experience difficulties organizing historical events chronologically. Data from questionnaires, interviews, and pretest results indicate that students' chronological thinking skills remain limited, with only 63% achieving adequate scores on the first indicator, 37% on the second, and 26% on the third. These findings highlight the necessity for developing concise, structured, and visually oriented iconic infographic media. The recommendation to develop Canva-based infographic media arises as an implication of needs analysis rather than empirical evidence of effectiveness, as this study is limited to the needs-analysis phase. Canva was selected for its user-friendly features, ready-to-use templates, and accessibility for teachers without specialized design skills.